The effect of moral identity on facial emotion processing in adolescents with hearing loss: an event-related potentials study - Jian, Mengyao; Hu, Yousong; Yang, Jinlin; Chen, Jun (Frontiers in Neuroscience, 2025)
ObjectiveThis study investigates how the moral characters of others influence the recognition of facial emotional expressions in adolescents with hearing loss (HL), and compares these effects with those in adolescents with typical hearing (TH).MethodsA moral priming paradigm was employed to explore the neural mechanisms underlying facial emotion perception (happy, neutral, and angry) in different moral contexts (high moral, low moral). Event-related potentials (ERP) were utilized to assess brain responses.ResultsAdolescents with TH evaluated emotional valence independently of moral context. In contrast, adolescents with HL judged faces with low moral levels more negatively. ERP analyses showed facial expression processing in adolescents with TH was not influenced by moral information, whereas adolescents with HL exhibited moral effects during both the middle (N2) and late stages (LPP) of processing.ConclusionThese findings underscore distinct neurocognitive mechanisms of emotion recognition in adolescents with HL and highlight the significant influence of moral identity on their emotional judgments.